Reproductive biology of the rock shrimp Sicyonia dorsalis (Decapoda: Penaeoidea) from the southeastern coast of Brazil - Castilho, A. L. [UNESP]; Furlan, Maysa [UNESP]; Costa, Rogério Caetano da [UNESP]; Fransozo, V. [UNESP] (Int Science Services/balaban Publishers, 2008)
Sicyonia dorsalis is not commercially exploited in Brazil, but it forms a critical link in marine food chains by converting detritus food sources into microorganism biomass that is available for higher trophic levels. We examined the reproductive biology of this species, sampled for five and a half years in a tropical locality, the southeastern coast of São Paulo (23 degrees S), Brazil. Monthly samples were taken from January 1998 to June 2003 at depths of 5 to 45 m. Degree of ovarian development was used to examine breeding in adult females. Recruitment was estimated by changes in proportion of individuals in juvenile size classes of carapace length (CL <= 8.2 mm) in relationship to the total number of individuals. The largest immature female measured 9.2 mm CL, but 75% of females were smaller than 7.3 mm CL. The largest immature male measured 6.8 mm CL. The relative frequency of reproductive females was negatively correlated with the relative frequency of recruitment (p <0.001). Reproductive females were found in every season, with peaks in December-February following the recruitment peak in March-June, and a second peak of spawning in May-July and of recruitment in September-November. The continuous reproductive pattern observed for S. dorsalis, combined with the hypothesis that during spring and summer the phytoplankton production is higher, when the South Atlantic central water mass intrudes into the region during upwelling events, suggests that food availability for protozoeal and mysis larvae may be an important selective factor shaping the seasonal breeding pattern for S. dorsalis. The classical paradigm of continuous reproduction at lower latitudes, with increased seasonality of the breeding period at higher latitudes, seems to be valid for this species.
Keywords: Penaeoidea; Sicyonia dorsalis; reproduction biology; reproductive pattern; recruitment; sexual maturity